Prevalence and Impact of Refractive Errors in School-Aged Children: A Cross-Sectional (The International Journal for Scientific Research, 2024)
This cross-sectional study aims to determine the prevalence and patterns of refractive errors among 700 schoolchildren aged 5-15 years in Al-Manara School, Tobruk, Libya. A comprehensive ophthalmic examination will be conducted to assess visual acuity and identify refractive errors. Academic performance will be evaluated by reviewing school records, including grades and standardized test scores. The impact of refractive errors on quality of life will be measured using a validated pediatric vision-related quality of life questionnaire. The study seeks to provide data on the burden of refractive errors and their effects on learning and daily living in this population. We hypothesize that uncorrected refractive errors will be associated with poorer academic achievement and reduced quality of life compared to peers without vision impairment. This research can highlight the need for regular vision screening and provision of spectacles for schoolchildren in Libya. Findings may guide education policy and school health programs to address this treatable cause of impaired classroom performance. The large sample size will allow for analysis of prevalence stratified by key demographics and characterization of the patterns of refractive errors in this geographic setting.
Keywords: Refractive Errors; School-Aged Children; Academic Performance; Quality of Life; Vision Screening; Cross-Sectional Study; Myopia; Hyperopia; Astigmatism; Visual Impairment